State and market: altering the boundaries and emerging new balances - Reddy, Y.V. (1999)
The concept of the mixed economy that we adopted was the right one. What is called for is a dynamic and bi-directional movement between the state and the market. The reform process in India has been able to capture the basic elements of this complex reality and there is, at least at the conceptual level, a pragmatic framework. There are emerging new balances and a dynamism has to be located in these new balances. Analysts need to understand these emerging new balances to appreciate the stability and pace of reform. - Reproduced
Keywords: Market economy